2023
DOI: 10.1038/s41598-023-29985-z
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness evaluation of risk-based breast cancer screening in Urban Hebei Province

Abstract: To evaluate the implementations of Cancer Screening Program in Urban Hebei and to model the cost-effectiveness of a risk-based breast Cancer Screening Program. Women aged 40–74 years were invited to participate the Cancer Screening Program in Urban Hebei form 2016 to 2020 by completing questionnaires to collect information about breast cancer exposure. Clinical screening including ultrasound and mammography examination were performed. We developed a Markov model to estimate the lifetime costs and benefits, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Second, for community servers in population-based EC screening, more attention and interventions should be paid to several vulnerable populations in health literacy to improve their compliance rate with endoscopic examinations. These populations included males, cigarette smokers, and those with low socioeconomic status, who had a higher risk of developing EC but lower compliance rates of endoscopic examinations, as observed in previous population-based EC screening studies [31,33,79]. In addition, optimization of the screening procedure, such as shortening the waiting time for endoscopic examinations, may be considered another effective measure to improve compliance, as indicated in population-based cancer screening programs [80].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, for community servers in population-based EC screening, more attention and interventions should be paid to several vulnerable populations in health literacy to improve their compliance rate with endoscopic examinations. These populations included males, cigarette smokers, and those with low socioeconomic status, who had a higher risk of developing EC but lower compliance rates of endoscopic examinations, as observed in previous population-based EC screening studies [31,33,79]. In addition, optimization of the screening procedure, such as shortening the waiting time for endoscopic examinations, may be considered another effective measure to improve compliance, as indicated in population-based cancer screening programs [80].…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the 66 included studies are outlined in Table S4 of Multimedia Appendix 1, and the summary characteristics about reporting compliance with endoscopy examinations and endoscopy findings are summarized in Table 1 and Table 2, A total of 2,472,920 asymptomatic individuals were included in 31 studies that reported compliance with endoscopy examinations, one of which reported data from both rural and urban China [11]. Therefore, 2,006,235 individuals were from high-risk areas during 1999-2017 (n=12) [6,10,[12][13][14][15][16][17][18][19][20][21], 125,473 individuals were from rural China during 2010-2017 (n=2) [11,22], and 341,212 individuals were from urban China during 2012-2019 (n=18) [11,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], as shown in Table 1 and Table S4 of Multimedia Appendix 1. The details of the high-risk assessment strategy to select targets to undergo further endoscopy screening are summarized in Table S5 of Multimedia Appendix 1.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound machines are comparatively more cost-effective and portable than mammography or magnetic resonance imaging (MRI) machines, considering their initial price and infrastructure requirements. The price of breast ultrasonography improves the practicality of including it in screening programs, particularly in places with low resources, hence guaranteeing wider availability of early detection techniques [ 16 , 18 , 19 , 26 , 45 ].…”
Section: Advantages Of Breast Ultrasound In Breast Cancer Screeningmentioning
confidence: 99%
“…This had resulted in insu cient evidence for policy recommendations. 5,[8][9][10] Breast cancer screening might be cost-effective in a Chinese setting for two reason. First, screening could detect patients early, enabling them to receive effective treatment and avoid serious health outcomes and cost expenditures.…”
Section: Introductionmentioning
confidence: 99%